The influence of local clothing brand product design in increasing brand awareness - Ahmad Ridwan Rais; Arief Budiman; Nizza Nadya Rachmani (Institute of Computer Science (IOCS), 2023)
Product design is one of the most important parts of the way of recognizing a brand product to improve brand awareness, which in this globalization era the appearance of a product greatly affects the interest of consumers to buy a product. Brand awareness plays an important role in maintaining consumer loyalty so that consumers still feel comfortable with the products offered. In Bandung City, Indonesia, there’s a competitive competition in global brand and local product, the innovation of local product and design play important role in raising brand awareness to compete the competition. This study aims to determine how much Local Clothing Brand product design effect on brand awareness. This study uses quantitative methods with a descriptive approach. Based research result it can be interpreted that the design has a contribution to the local product brand awareness variable of 78.2%, and discoveries likewise recommend neighborhood style clothing makers ought to accentuate creation quality, improve plan and item credits, and guarantee item customization because of customer and market needs. As a matter of fact, clients will foster brand dependability and positive informal as indicated by their previous encounters because of good quality items that are likewise creative and satisfy their assumptions.